Six business model recommendations for ACP digital agribusiness entrepreneurs - Lohento, Ken; Tossou, Hermann S. (Technical Centre for Agricultural and Rural Cooperation, 2018)
CTA's Ken Lohento addressing agripreneurs and innovators at the 2017 pitch Agrihack competitions.